Designing an ESP- Syllabus Framework Based on Conducting of an Effective Target Situation Needs Analysis a Case Study of Abu Dhabi Police Traffic Officers - Khairy, Hassan Mohamed (Journal of Humanities & Social Sciences, 2017)
This study aims at analyzing the target situation needs for Abu Dhabi Police traffic Staff to suggest an ESP- base syllabus framework. These needs will be employed to designs an ESP- Syllabus. A questionnaire was used to collect data from the participants, after analyzing the data collected, it was revealed that English language in general is of great importance to traffic police. Participants who were 50 police men working in traffic department ensured that some language functions should be included in the suggested ESP-based syllabus. In addition to some language sub-skills they rated as very important, furthermore, they questionnaire evaluated some language difficulties they may encounter while they perform their duties.